Microsoft Power BI quick start guide : build dashboards and visualizations to make your data come to life - Knight, Devin; Knight, Brian, 1976-; Pearson, Mitchell; Quintana, Manuel (Packt Publishing, 2018)
Microsoft Power BI is a cloud-based service that helps you easily visualize and share insights from your organization's data. This book will get you started with Business Intelligence using the Power BI tool, covering essential concepts like installation, building basic dashboards and visualizations to make your data come to life.